Studying the usability of recycled aggregate to produce new concrete - Qasim, Ola Adel; Hilal, Nahla Naji; Al Biajawi, Mohammad Ismail Yousef; Sor, Nadhim Hamah; Tawfk, Taher A. (Institute for Ionics, 2024)
One of the most signifcant environmental issues worldwide is garbage, particularly waste from construction materials, which is generated in substantial numbers. However, in the building industry, the signifcant extraction of natural resources such as cement, natural sand, and natural gravel poses a critical environmental challenge, depleting these resources at an alarming rate. There are some solutions that developed countries are resorting to, namely the division of construction waste into groups, where it is reused under the name of recycling construction waste to produce new, environmentally friendly building materials. The aim of this research includes a laboratory process study as it includes the use of the following ratios: 0, 10, 20, 30, 40, 50, 60, 70, 80, 90, and 100%, under the process of replacing coarse plain aggregates including coarse recycled aggregates and studying the most important mechanical properties of concrete. This research was carried out using fresh concrete properties such as workability tests and hardened concrete properties such as compressive strength, splitting, and fexural tensile strength examined at the durations of 7, 14, and 28 days. The research includes the investigation of the three main properties of concrete. After conducting the tests, the results have shown that the main property of recycled concrete is lower strength than that of conventional concrete, but it can be said that it is within the limits that can be used for construction. The results also showed that compared to normal aggregates, development in the recycled aggregate percentage rates reduces the operational workability of concrete. The research proved that the maximum decrease in compressive, fexural, and tensile strength, density and the slump were 19.4, 18.3, 19.6, 19.5, and 25.0% respectively compared to the control concrete samples.